Breeding Whooper Swans Cygnus cygnus in the Baltic states, 1973â€“2013: result of a 207 re-colonisation - Boiko, Dmitrijs; Kamp-Persson, Hakon; MorkÅnas, Julius (Wildfowl, 2014)
A review of the literature on Whooper Swans Cygnus cygnus breeding in the Baltic states indicates that the swans are recolonising areas where they once bred historically. In recent years, the number of breeding birds has increased from two pairs in 1973 to 600–670 pairs in 2013, though the growth rate has slowed in Latvia, and maybe also in Estonia and Lithuania. There was a clear latitudinal difference in the choice of breeding habitats: in Estonia, the Whooper Swans preferred bogs, lakes and coastal waters, while the vast majority of all pairs in Latvia and Lithuania were found in fishpond complexes and wetlands associated with beaver dams.